2016
DOI: 10.1093/abbs/gmw052
|View full text |Cite
|
Sign up to set email alerts
|

R-loop: an emerging regulator of chromatin dynamics

Abstract: The dynamic structure of chromatin, which exists in two conformational states: heterochromatin and euchromatin, alters the accessibility of the DNA to regulatory factors during transcription, replication, recombination, and DNA damage repair. Chemical modifications of histones and DNA, as well as adenosine triphospahate-dependent nucleosome remodeling, have been the major focus of research on chromatin dynamics over the past two decades. However, recent studies using a DNA-RNA hybrid-specific antibody and next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 103 publications
1
32
0
Order By: Relevance
“…5A). A previous study showed that R-loops with the H3K9me2 mark can repress FMR1 gene expression (Colak et al 2014), and this scenario aligns well with the results from other studies (Al-Hadid and Yang 2016;Sanz et al 2016;García-Benítez et al 2017;García-Pichardo et al 2017), which found that epigenetic marks are linked to R-loop formation. We validated this finding experimentally in methylation-deficient mutants using dot blot and western blotting ( Fig.…”
Section: The Coordination Of R-loops and Histone Markssupporting
confidence: 90%
See 1 more Smart Citation
“…5A). A previous study showed that R-loops with the H3K9me2 mark can repress FMR1 gene expression (Colak et al 2014), and this scenario aligns well with the results from other studies (Al-Hadid and Yang 2016;Sanz et al 2016;García-Benítez et al 2017;García-Pichardo et al 2017), which found that epigenetic marks are linked to R-loop formation. We validated this finding experimentally in methylation-deficient mutants using dot blot and western blotting ( Fig.…”
Section: The Coordination Of R-loops and Histone Markssupporting
confidence: 90%
“…Because the technology to partially deplete R-loops on a genome-wide scale is not yet available, we could not verify the causal effects of R-loops on epigenetic modifications on a large scale, although we indeed provided multiple lines of computational evidence to support this. In addition, two other studies have shown that R-loops have effects on histone modifications (Castellano-Pozo et al 2013;Al-Hadid and Yang 2016).…”
Section: The Coordination Of R-loops and Histone Marksmentioning
confidence: 98%
“…In fact, not only an R-loop per se but also a stalled RNA polymerase machinery may impede DNA replication and lead to further R-loop accumulation ( García-Muse and Aguilera, 2016 ). Moreover, R-loops have been shown to trigger chromatin modifications, mainly including chromatin condensation ( Castellano-Pozo et al, 2013 ; Al-Hadid and Yang, 2016 ; García-Pichardo et al, 2017 ; Figure 2 ), and this event seems to be a key requisite for compromising genome stability ( García-Pichardo et al, 2017 ).…”
Section: R-loops As Sources Of Genome Instabilitymentioning
confidence: 99%
“…Similarly, in yeast and mammalian cells R-loop association with chromatin modification and non-coding RNA mediates termination of transcription (44)(45)(46)(47). Indeed, R-loop and chromatin modification might be a widespread association (48)(49)(50), since the hybrids can be found throughout some protein-coding genes, rather than being limited to promoters and terminators (51,52).…”
Section: Introductionmentioning
confidence: 99%